Indo-Iranian Journal - Bakker, H. T.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: .)
Indo-Iranian Journal, founded in 1957, focuses on the ancient and medieval languages and cultures of South Asia and of pre-islamic Iran. It publishes articles on Indo-Iranian languages (linguistics and literatures), such as Sanskrit, Avestan, Middle Iranian and Middle & New Indo-Aryan. It publishes specialized research on ancient Iranian religion and the Indian religions, such as the Veda, Hinduism, Jainism and Buddhism (including Tibetan). The journal welcomes epigraphical studies as well as general contributions to the understanding of the (pre-modern) history and culture of South Asia. Illustrations are accepted. A substantial part of Indo-Iranian Journal is reserved for reviews of new research. Twice a year it contains a detailed bibliography of all publications received. The Journal publishes articles in English, French and German.
Keywords: Philosophy, Asian; Indo-Iranian languages; Non-Western Philosophy; Indo-Iranian Languages